The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0897190013514091
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Anticoagulation Stewardship Program at a Large Tertiary Care Academic Institution

Abstract: Pharmacist-directed anticoagulation management services (AMSs) have been shown to significantly lower anticoagulation-related mortality, length of hospital stay, bleeding complications, blood transfusion requirements, and cost of therapy. AMSs are only 1 component of an anticoagulation stewardship program. Frequently, stewardship programs are limited to inpatient populations. Incorporating components that facilitate transition to outpatient status will ideally encompass complete care. The purpose of this progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The study also reported that more patients in the traditional physician-monitored group had sub-therapeutic INR measurement ≤1.5 and they did not return as quickly for dosage adjustment ( Poon et al, 2007 ). In addition, a prospective study by Padron and Miyares (2013) carried out in the Jackson Memorial Hospital, Miami, reported that involvement of pharmacists in anticoagulation management can enhance standards of care and ensure the protocols were upheld, therefore improving patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that more patients in the traditional physician-monitored group had sub-therapeutic INR measurement ≤1.5 and they did not return as quickly for dosage adjustment ( Poon et al, 2007 ). In addition, a prospective study by Padron and Miyares (2013) carried out in the Jackson Memorial Hospital, Miami, reported that involvement of pharmacists in anticoagulation management can enhance standards of care and ensure the protocols were upheld, therefore improving patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty studies evaluated targeted drug programs (Table S3). The majority of these evaluations utilized study designs at high risk of bias. Nonrandomized posttest designs with a historical control comprised 55% studies, followed by single‐group posttest (15%), single‐group pretest‐posttest (10%), and nonrandomized pretest‐posttest with a historical control (5%).…”
Section: Resultsmentioning
confidence: 99%
“…In one survey sent to members of the America College of Pharmacists practice and research networks for cardiology, critical care and general internal medicine, only 4 of 25 responding member centres indicated that their antithrombotic service was multidisciplinary 7. Padron and Miyares8 describe an expanded antithrombotic stewardship, including both DOAC treatment and facilitating care after hospital discharge. It concerned a US single-centre pharmacist-directed stewardship.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions consisted of changes to a more appropriate antithrombotic therapy according to guidelines and dosing corrections. The length of hospital stay was reduced by 1.5 days and cost-savings were $270.320 ($661 per patient) in 1.5 years 8. Tedders and colleagues evaluated the impact of an inpatient, pharmacist-led dabigatran management protocol.…”
Section: Introductionmentioning
confidence: 99%